Methodological Characteristics of Ensuring the Integration of Physical Education in the System of School Education (Journal of Pedagogical Inventions and Practices, 2023)
Possibilities of independent and practical mastery of the forms distributed during the academic year based on the integration of the content of pedagogical features and components of complex development such as healthy lifestyle and work ethic in the educational process of developing the physical qualities of children aged 15-17 and teaching them to act.